International Students’ Adaptation in Russia: its Varying Due to the Student’s Culture of Origin - V. A. Fedotova (Вестник Кемеровского государственного университета, 2022)
The study aims to identify peculiarities of sociocultural adaptation (factors, coping strategies and anticipatory competence) of students from India, China and Arab countries. The research is based on the data obtained from the first-, second- and third-year students from India (73 respondents), China (45 respondents), Arab countries (64 respondents). The “Russian language proficiency” factor shows more significance for students from India and China, compared to students from Arab countries. Students from China, India and Arab countries tend to start and maintain relationships, to participate in academic activities, to have hobbies and interests and interact with other students. The prosocial coping strategy is predominant for Arab, Indian and Chinese students, regardless of their culture of origin, which proves  universality of the strategy. Representatives of a polychronic culture (students from Arab countries and India) lack temporal anticipatory competence,with Arab students showing the lowest value of this parameter. Chinese  students differ from representatives of a polyactive culture (Arab students) or a reactive-polyactive culture (Indian students) as they can hardly predict how a person they know would act in a certain situation.